Feasibility and Acceptability of Metformin to Augment Low Milk Supply: A Pilot Randomized Controlled Trial. (May 2019) - Nommsen-Rivers, Laurie; Thompson, Amy; Riddle, Sarah; Ward, Laura; Wagner, Erin; King, Eileen
Background: Metformin improves insulin action, but feasibility in treating low milk supply is unknown. Research aim: To determine the feasibility of a metformin- versus -placebo definitive randomized clinical trial in women with low milk production and signs of insulin resistance. Methods: Pilot trial criteria included: Mother 1–8 weeks postpartum (ideally 1–2 weeks), low milk production, and ≥1 insulin resistance sign; and singleton, healthy, term infant. Eligible mothers were randomly assigned 2:1 (metformin:placebo) and instructed in frequent milk removal for 28 days with option to stop at 14 days. Results: From 02/2015 through 06/2016, we screened 114 women, completed baseline assessments on 46, and trialed 15 (median, 36 days postpartum). Comparing metformin-assigned ( n = 10) to placebo ( n = 5), 70% versus 80% continued to day 28; peak median change in milk output was +8 versus –58 mL/24 hr ( p = .31) and 80% peaked at Day 14 for both groups; 0% versus 20% desired to continue assigned drug after study completion; 44% versus 0% reported nausea/vomiting. Post-hoc, median peak change in milk output was +22 (metformin completers, n = 8) versus –58 mL/24 hr (placebo + non-completers, n = 7, p = .07). At baseline assessment, median milk production was significantly lower in those with ( n = 31), versus those without ( n = 15) signs of insulin resistance ( p = .002). Conclusions: Although results trend toward hypothesized direction, trial feasibility concerns include late enrollment and only 20% of metformin-assigned participants sustaining improved milk output to Day 28, with none perceiving metformin worthwhile. Better tools are needed to identify and treat metabolically-driven low milk production. Registered at ClinicalTrials.gov (NCT02179788) on 02/JUL/2014.